The Efficacy of Cancer Immunotherapies Is Compromised by Helicobacter pylori Infection - Oster, Paul; Vaillant, Laurie; McMillan, Brynn; Velin, Dominique (Frontiers in Immunology, 2022)
Helicobacter pylori colonizes the human gastric mucosa with a high worldwide prevalence. Although the majority of cases remain asymptomatic for decades, H pylori infection is associated with increased occurrence of peptic ulcers and more seriously, with the development of gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. Using a variety of mechanisms, H pylori locally suppresses the function of the host immune system to establish chronic infection. Systemic immunomodulation has been observed in both clinical and pre-clinical studies, which have demonstrated that H pylori infection is associated with reduced incidence of inflammatory diseases, such as asthma and Crohn’s disease. The introduction of immunotherapies in the arsenal of anti-cancer drugs has revealed a new facet of H pylori-induced immune suppression. In this review, we will describe the intimate interactions between H pylori and its host, and formulate hypotheses describing the detrimental impact of H pylori infection on the efficacy of cancer immunotherapies.